The distribution of tick-borne encephalitis virus genotypes in different types of landscapes of Eastern Siberia - M. M. Verkhozina (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
To find out what is the role of some environmental factors in the formation of a heterogeneous viral population, the analysis of the distribution of tick-borne encephalitis virus (TBEV) genotypes in different types of landscapes of Eastern Siberia has been carried out. In our study, it was shown that TBEV area in all investigated landscapes of Eastern Siberia is represented not only by TBEV of genotype 3, absolute dominance of which is noted in the studied regions, regardless the landscapes where the foci are located, but also by strains of other genotypes. The relationship between genotypes 1,3 and "polytypic" strains with a certain type of landscape and the degree of their development by man has not been established. The prevailing number of strains of TBEV genotype 5 is isolated from the material collected in the Transbaikalia, in the landscapes of the mountain taiga. They, as well as the strain of genotype 4, are found in the foci, where joint circulation of several TBEV genotypes is noted. The strains of TBEV genotype 2 were revealed in the landscapes of plains and plateaus taiga and insular steppes and forest steppes of the southern part of the Baikal region. Moreover, the detection of RNA of TBEV genotype 2 in the "polytipic" 763-87 and 765-87 strains isolated in the floodplain and forest-steppe landscapes of the Barguzin hollow does not exclude the possibility of circulation of TBEV genotype 2 in the Transbaikalian foci. The greatest genetic heterogeneity of TBEV is observed in natural foci located along Lake Baikal and in the southeastern part of Transbaikalia.